Education as Morals in Dewey’s Philosophy - Friedman, Robin (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2024)
This article explores Dewey's understanding of the nature of education through three seminal works written over a 32-year period. In Democracy and Education (1916) Dewey developed a concept of education which can be understood through two German words for education, Erziehung and Bildung. Through considering the approach to these concepts by two Dewey scholars, Gert Biesta and Dietrich Benner, the first section of this article seeks to explore Dewey's understanding of education and its relationship to democracy. The second section of the article carries the study forward to Dewey's Human Nature and Conduct (1922) to show how Dewey conceived of education even more broadly and equated it with morals. The concepts of Erziehung and Bildung also are important in this section, as they are expanded to show that, for Dewey, education was a guide in how to live. The third section of the article expands the concept of education still further to view education as philosophy. This section discusses Dewey's book Experience and Education (1938) which he wrote in light of his metaphysical study Experience and Nature (1925). Dewey expanded his understanding of education beyond both Erziehung and Bildung and beyond morals to develop an understanding of education as based upon a philosophical consideration of experience. The goal of the article is to show the breadth of Dewey's understanding of education and to show how his view of education forms the basis of a broad philosophical view of life.